Black soldier fly larvae meal and fat as a replacement for soybeans in organic broiler diets: effects on performance, body N retention, carcase and meat quality. Issue 5 (3rd September 2022) - Heuel, M.; Sandrock, C.; Leiber, F.; Mathys, A.; Gold, M.; Zurbrüegg, C.; Gangnat, I. D. M.; Kreuzer, M.; Terranova, M.
ABSTRACT: 1. Due to the increasing global demand for more sustainably produced animal protein, there is an intensive search for feeds to replace soybeans. Black soldier fly larvae (BSFL) appear to have great potential for replacing soybeans in poultry diets. The main objective of this study was to determine if the nutritional value of BSFL is superior to soybeans when feeding organic broilers, since smaller amounts of BSFL could replace the soybean content in the feed, thus saving even more resources. 2. Eighty Hubbard S757, a slow growing organic broiler type, were fattened for 63 d, spending the last 49 d on one of five diets. Two soybean cake- and soybean oil-based diets (SS, SS-) were compared with three diets based on partially defatted BSFL meal and BSFL fat from two origins (AA-, AB-, BB-). Different from diet SS, diets SS-, AA-, AB-and BB- were designed with approximately 20% less lysine and methionine. Growth ( n = 16), metabolisability, body nitrogen retention, carcase and meat quality ( n = 8) were evaluated. 3. Broilers of the insect-based feeding groups, AA- and AB-, grew similarly well compared to those of group SS. They also retained more nitrogen in the body than those fed BB- and SS-. Breast meat yield was higher with AA- and AB- than with BB- and SS-, but still lower than with SS. Dietary variations in physicochemical meat quality were of low practical relevance. Diet BB- resulted in a more yellow skin and meat. The fatty acid profile of the breast meat lipids reflected the high lauric acid proportion of the BSFL lipids, resulting in up to 80 times higher proportions than when feeding the soybean-based diets. 4. The results indicate that high-quality BSFL, depending on their origin, may indeed be superior to soybean protein, but that the meat lipids from BSFL-fed broilers can contain significant amounts of lauric acid, which, from a human nutrition perspective, could have a negative impact on meat quality.